A randomised, controlled clinical trial of narrowband UVB phototherapy for clinically isolated syndrome: The PhoCIS study. Issue 2 (April 2018) - Hart, Prue H; Jones, Anderson P; Trend, Stephanie; Cha, Lilian; Fabis-Pedrini, Marzena J; Cooper, Matthew N; d'Este, Catherine; Geldenhuys, Sian; Carroll, William M; Byrne, Scott N; Booth, David R; Cole, Judith M; et al.
Background: The natural history of multiple sclerosis (MS) typically presents with the clinically isolated syndrome (CIS), an episode of neurological symptoms caused by central nervous system inflammation or demyelination that does not fulfil the diagnostic criteria for MS. Objective: As preclinical studies have suggested that exposure to ultraviolet radiation (UVR) could regulate the development of MS, thePho totherapy forCIS (PhoCIS trial) was established to examine the effects of narrowband UVB phototherapy on patients with CIS, and their conversion to MS. Methods: Of the 20 participants, half received 24 sessions of narrowband UVB exposure over eight weeks; participants in both arms were followed for 12 months. All participants were supplemented to 25-hydroxyvitamin D3 levels of >80 nmol/l. Results: By 12 months, 100% of those in the no phototherapy arm and 70% in the phototherapy arm had converted to MS, although this difference was not statistically significant. Conclusion: This study provides a basis for further studies to determine if there are any benefits of the therapeutic effects of narrowband UVB radiation on MS progression.